THE EFFECTIVENESS OF GROUP COUNSELING WITH CBT MUSIC THERAPY TECHNIQUES TO REDUCE BOREDOM OF CLASS VIII STUDENTS AT MADRASAH TSANAWIYAH GINTANGAN.: EFEKTIVITAS KONSELING KELOMPOK PENDEKATAN COGNITIVE BEHAVIOR THERAPY (CBT) TEKNIK TERAPI MUSIK UNTUK MENGURANGI KEJENUHAN BELAJAR SISWA KELAS VIII DI MADRASAH TSANAWIYAH GINTANGAN - Abdul Munir; Heriberthus Wicaksono,; Ahmad Sulthoni, (Program Studi Bimbingan dan Konseling, 2023)
The research was conducted to determine the effectiveness of CBT group counseling music therapy techniques to reduce the boredom of learning for class VIII students at MTs Gintangan. The research used pre-experiment design one group pretest and posttest design. The sample was selected using nonprobability sampling design technique using purposive sampling. The data collection techniques used were questionnaires, observations, and interviews. Researchers used data analysis techniques with the SPSS 2.5 for windows test. The results showed that CBT group counseling with music therapy techniques proved effective in reducing the boredom of learning for class VIII students. This is reinforced from the results of the Paired Samples Statistic method hypothesis test obtained the mean value of pretest = 119.66 and at posttest = 55.16. There was a decrease in the value of students' feelings of learning saturation, which was initially high, to decrease after getting treatment in the form of group counseling in the form of CBT approaches to music therapy techniques